The Role of Job Satisfaction to Reduce Nurse Turnover Intention: A Systematic Review - Dewanti, Nisa; Purwanza, Sena Wahyu; Prakosa, Mira Melynda (Universitas Airlangga, 2023)
Introduction: Job satisfaction is a condition in which a person feels positive about the job and its characteristics. The conditions are synonymous with satisfying, happy, and grateful. A person with high job satisfaction tends to stay longer in the organization and supports the organization. The purpose of systematic review aims to search published articles on job satisfaction among nurses. Methods: This study applied a systematic review. Literature was searched in three databases namely PubMed, Science Direct, and Semantic Scholar with keywords